(untitled) (Konturen, 2020)
In his work Ideas for a Philosophy of Human History (1784-1791), the preacher and philosopher Johann Gottfried Herder deals critically with the philosophy of Enlightenment, in which he sees the seed of a racial and cultural classification that considers peoples outside Europe as inferior. This centrally included Africa and its inhabitants as represented by German philosophers. Such a way of imagining Africa, widely shared amongst thinkers of the Enlightenment, echoes still today in various representations in the Western media, and could even serve as an explanation of the current migration drama in the Mediterranean. Herder, who was well informed of these representations in his own day, attempted, in Ideas, to deconstruct the then prevalent image of Africa and its peoples, and thereby entered into an intellectual dispute with his philosophical contemporaries, whose position was to reaffirm the supremacy of European culture and soe justify slavery and colonialism. This paper first focuses on Herder’s context, then explains his positions and his work, and shows how his attempt ended in a de-construction of the «Africa» of the Enlightenment.